Pediatric Uroradiology - Fotter, Richard.; Fotter, Richard. (Diagnostic Imaging, 2008)
Since the first edition of Pediatric Uroradiology, very significant advances have been made in the imaging and treatment of common and important pediatric urologic disorders such as vesicoureteric reflux, urinary tract infection, and upper urinary tract dilatation. This revised and extended version takes full account of the sometimes dramatic changes. Where appropriate, new contents have been included, e.g., on genetics, while other information that continues to be pertinent has been retained. This book describes in detail all aspects of pediatric uroradiology. While it is written primarily from the point of view of the radiologist, it includes essential information for the pediatrician, pediatric surgeon, and urologist. It is specifically designed to aid the clinician in decisions on imaging management. The newest techniques and the changing relevance of imaging and interventional procedures are presented, and the diverse problems associated with the changing anatomy, physiology, and pathophysiology from the newborn period to adulthood are explained. The whole spectrum of imaging features of agenesis, anomalies, dysplasia, parenchymal diseases, neoplastic diseases, stone disease, renal vascular hypertension, renal failure, renal transplantation, and genitourinary trauma is covered. Individual chapters are devoted to vesicoureteric reflux, urinary tract infection, upper urinary tract dilatation, voiding dysfunction, and neurogenic bladder. A new chapter on the clinical management of common nephrourologic disorders, with the subtitle "guidelines and beyond," explains how imaging is embedded in the whole process of clinical management today. Short conclusions are included at the end of chapters and sections to provide the reader with the key information on the specific topic under consideration. This book is dedicated to children – everywhere.